Correlation of measurable serum markers of inflammation with lung levels following bilateral femur fracture in a rat model - Benjamin W Sears (Dove Medical Press, 2010)
Benjamin W Sears1, Dustin Volkmer1, Sherri Yong2, Ryan D Himes1, Kristen Lauing1, Michele Morgan1, Michael D Stover1, John J Callaci11Department of Orthopaedics, 2Department of Pathology, Loyola University Medical Center, Maywood, IL, USAIntroduction: Evaluation of the systemic inflammatory status following major orthopedic trauma has become an important adjunct in basing post-injury clinical decisions. In the present study, we examined the correlation of serum and lung inflammatory marker levels following bilateral femur fracture.Materials and methods: 45 Sprague Dawley rats underwent sham operation or bilateral femoral intramedullary pinning and mid-diaphyseal closed fracture via blunt guillotine. Animals were euthanized at specific time points after injury. Serum and lung tissue were collected, and 24 inflammatory markers were analyzed by immunoassay. Lung histology was evaluated by a blinded pathologist.Results: Bilateral femur fracture significantly increased serum markers of inflammation including interleukin (IL)-2, IL-6, IL-10, GM-CSF, KC/GRO, MCP-1, and WBC. Femur fracture significantly increased serum and lung levels of IL-1a and KC/GRO at 6 hours. Lung levels of IL-6 demonstrated a trend towards significance. Histologic changes in pulmonary tissue after fracture included pulmonary edema and bone elements including cellular hematopoietic cells, bone fragments and marrow emboli.Discussion and conclusion: Our results indicate that bilateral femur fracture with fixation in rats results in increases in serum markers of inflammation. Among the inflammatory markers measured, rise in the serum KC/GRO (CINC-1), a homolog to human IL-8, correlated with elevated levels of lung KC/GRO. Ultimately, analysis of serum levels of KC/GRO (CINC-1), or human IL-8, may be a useful adjunct to guide clinical decisions regarding surgical timing.Keywords: blunt trauma, injury, cytokine, IL-8, bone marrow emboli